Systemic Risk Dimensions in the Hungarian Banking and Insurance Sector - Szüle, Borbála (Public Finance Quarterly, 2023)
The consecutive financial crises have made the analysis of the systemic risks of financial institutions increasingly important worldwide. The researches so far have been primarily focusing on the banking sector, but insurance companies have also been given an increasing attention. Based on past literature, systematic risk can be measured in a variety of ways, and one of the options is the calculation of the indicators typical of return comovement. This study compares the dimensions calculated by the multidimensional scaling of returns in the banking and insurance sector. The results suggest that return dimensions in the Hungarian banking and insurance sector (related to systemic risk) are not completely independent, and, compared to the banking sector, the return comovement related systemic risk is lower in the insurance sector.